Studi Kasus: Addictive Media Sosial, Peer Acceptence dan Well Being pada Siswa Sekolah Dasar - Wicaksani, Alifia Cahya; Khoiriyah, Ika Silfiana A. (Universitas Muria Kudus, 2020)
This study aims to determine the correlation of addictive social media, peer acceptence, and well-being in elementary school students.The method used in this research uses a mix method which is done quantitatively and qualitatively. Quantitative method is done by giving questionnaires from each variable and then carried out by statistical tests using product moment correlation analysis. For qualitative interviews were conducted with elementary school students at SDN 1 Rejosari with in-depth interviews to find the meaning obtained.The results showed that r1 = -0.205, r2 = 0, 233 and r3 = 0.378. In ri there is no significant relationship because p bigger than 0.005 but the closeness is negative -0.205 so there is no positive relationship between addictive social media with well-being, r2 shows there is a positive relationship between addictive social media with peer acceptance and r3 indicates a positive relationship between peer acceptence and well-being of elementary school students. In the case of elementary school students who cause addictive because it is closely related to peer friendship so it will connect to the level of well-being.